Development of high‐speed mobile radio communication systems using 40 GHz frequency band. Issue 7 (30th July 2016) - Tsuji, H.; Tsukamoto, K.; Suzuki, K.; Nagayama, H.
Abstract: We investigated a broadband communication system for high‐speed vehicles such as airplane in which the millimeter wave band (40 GHz band) facilitates broadband wireless communications. Some developments and evaluations toward such the realization have been conducted. This paper introduces examples and results of the efforts to realize high‐speed mobile communication systems that take advantage of the features of the millimeter wave band along with overcoming the challenges associated with high‐frequency band development. Key Points: The paper shows research and development of broadband mobile communication systems using the millimeter wave band of 40 GHz band for railway and airplane systems The paper shows that the millimeter wave propagation is suit for condition of tunnel The paper shows that the antenna diversity technique can mitigate the deep drop of received power from multipath effects